Composite material and preparation method thereof

By introducing AES into PMMA/ASA composites and achieving micro-crosslinking with ASA, the problem of insufficient heat resistance of composites is solved, significantly improving its heat resistance and meeting the requirements of high-temperature applications.

CN119798903AActive Publication Date: 2025-04-11CHERY AUTOMOBILE CO LTD

Patent Information

Application Number
CN202510293142.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-13
Publication Date
2025-04-11
Estimated Expiration
2045-03-13

AI Technical Summary

Technical Problem

The existing PMMA/ASA composite materials have poor heat resistance and cannot be used in high temperature scenarios.

Method used

AES is introduced as a co-toughening agent for ASA, and the micro-crosslinking of AES and ASA is achieved through crosslinking agents, improving the heat resistance of composite materials.

Benefits of technology

While ensuring toughness, the heat resistance of composite materials is significantly improved, and the Vica softening temperature can reach 105℃, meeting the use requirements of the body exterior parts.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention discloses a composite material and a preparation method thereof, and belongs to the technical field of resin. AES is introduced into the composite material to serve as a co-toughening agent of ASA, micro-crosslinking of AES and ASA is achieved through the cross-linking agent by means of ethylene propylene rubber in an AES molecular structure, and the heat resistance of the whole system can be improved through the toughening agent obtained after micro-crosslinking on the premise that the toughness is guaranteed. The vicat softening temperature of the composite material can reach 105 DEG C, and the composite material can meet the use requirements of exterior trimming parts of automobile bodies.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of resin technology, and in particular to a composite material and a preparation method thereof. Background Art

[0002] PMMA (Polymeric Methyl Methacrylate) is a material with excellent light resistance. It can meet the lighting requirements of the car body exterior and is used in the car body exterior, such as in the car exterior lights. However, the PMMA material itself is very brittle and has low impact strength, so it cannot be used in scenes with force or collision tests. The current mainstream method is to compound PMMA with ASA (acrylonitrile-styrene-acrylate copolymer) to increase the toughness of PMMA by adding ASA to PMMA to expand its scope of use. However, the heat resistance of ASA material is significantly lower than that of PMMA material. After adding ASA material to PMMA material, the Vicat softening point of PMMA material will be reduced, resulting in poor heat resistance of PMMA / ASA composite materials, which cannot be used in high temperature scenes. Summary of the invention

[0003] The embodiment of the present application provides a composite material and a preparation method thereof, which can improve the heat resistance of the composite material. The technical solution is as follows: In one aspect, a composite material is provided, the composite material comprising the following components in parts by weight: 50-90 parts of polymethyl methacrylate PMMA, 10-40 parts of acrylonitrile-styrene-acrylate copolymer ASA, 5-20 parts of ethylene-propylene-styrene-acrylonitrile copolymer AES, 0.1-3 parts of crosslinking agent, 0.1-1 parts of heat stabilizer, 1-10 parts of compatibilizer, and 0.1-3 parts of light stabilizer.

[0004] In a possible implementation, the mass fraction of ethylene propylene rubber in the AES is 20% to 50%.

[0005] In another possible implementation, the melt index of the PMMA is 0.5-20 g / min.

[0006] In another possible implementation, the mass fraction of the acrylic rubber in the ASA is 20% to 60%.

[0007] In another possible implementation, the cross-linking agent includes at least one of cumene peroxide, hydrogen peroxide, potassium peroxide, and sodium peroxide.

[0008] In another possible implementation, the compatibilizer is a binary copolymer of any two components of acrylonitrile, styrene and maleic anhydride; or a terpolymer of acrylonitrile, styrene and maleic anhydride.

[0009] In another possible implementation, the mass fraction of the maleic anhydride in the terpolymer or the binary copolymer containing the maleic anhydride is 15% to 50%.

[0010] In another possible implementation, the heat stabilizer includes at least one of a hindered phenol heat stabilizer and a hypophosphite heat stabilizer.

[0011] In another possible implementation, the light stabilizer includes at least one of a hindered amine light stabilizer and an ultraviolet absorber.

[0012] In another aspect, a method for preparing a composite material is provided, the method comprising: According to the weight proportion of each component, the AES and the ASA are first mixed uniformly, and then the cross-linking agent and 0.05-0.4 parts of the heat stabilizer are added and continued to be mixed uniformly to obtain a first mixed material; Adding the first mixed material into a twin-screw extruder at an extrusion temperature in the range of 190-230° C. to obtain a mixture; The mixture is uniformly mixed with the PMMA, the compatibilizer, the light stabilizer and 0.05-0.6 parts of the heat stabilizer to obtain a second mixed material; The second mixed material is added into the twin-screw extruder at an extrusion temperature in the range of 190-250° C. to obtain the composite material.

[0013] The embodiment of the present application provides a composite material, in which AES is introduced as a co-toughening agent of ASA, and the ethylene-propylene rubber in the molecular structure of AES is used to achieve micro-crosslinking of AES and ASA through a crosslinking agent. The toughening agent after micro-crosslinking can improve the heat resistance of the entire system while ensuring toughness. Among them, the Vicat softening temperature of the composite material can reach 105°C, which can meet the use requirements of vehicle body exterior trims.

[0014] It is to be understood that the foregoing general description and the following detailed description are exemplary only and are not restrictive of the present disclosure. DETAILED DESCRIPTION

[0015] In order to make the technical solutions and advantages of the present application clearer, the implementation methods of the present application are described in further detail below.

[0016] On the one hand, an embodiment of the present application provides a composite material, which includes the following components in parts by weight: PMMA 50~90 parts, ASA 10~40 parts, AES (ethylene-propylene-styrene-acrylonitrile) 5~20 parts, cross-linking agent 0.1~3 parts, heat stabilizer 0.1~1 parts, compatibilizer 1~10 parts, light stabilizer 0.1~3 parts.

[0017] The weight proportion of PMMA may be 50, 55, 60, 65, 70, 75, 80, 85, or 90. Specifically, the weight proportion of PMMA may be 55 to 75.

[0018] The weight proportion of ASA can be 10 parts, 15 parts, 20 parts, 25 parts, 30 parts, 35 parts, 40 parts. Specifically, the weight proportion of ASA can be 20-30 parts.

[0019] The weight proportion of AES can be 5 parts, 6 parts, 8 parts, 10 parts, 12 parts, 15 parts, 18 parts, or 20 parts. Specifically, the weight proportion of AES can be 6 to 15 parts.

[0020] The weight proportion of the crosslinking agent may be 0.1 part, 0.3 part, 0.5 part, 0.8 part, 1 part, 1.5 parts, 1.8 parts, 2 parts, 2.5 parts, or 3 parts. Specifically, the weight proportion of the crosslinking agent may be 0.3 to 0.8 parts.

[0021] The weight portion of the heat stabilizer can be 0.1 part, 0.2 part, 0.3 part, 0.4 part, 0.5 part, 0.6 part, 0.7 part, 0.8 part, 0.9 part, or 1 part. Specifically, the weight portion of the heat stabilizer can be 0.1 to 0.5 part.

[0022] The weight proportion of the compatibilizer can be 1 part, 2 parts, 3 parts, 4 parts, 5 parts, 6 parts, 7 parts, 8 parts, 9 parts, 10 parts. Specifically, the weight proportion of the compatibilizer can be 3 to 5 parts.

[0023] The weight proportion of the light stabilizer can be 0.1 part, 0.3 part, 0.5 part, 0.8 part, 1 part, 1.5 parts, 1.8 parts, 2 parts, 2.5 parts, 3 parts. Specifically, the weight proportion of the light stabilizer can be 0.5 to 1 part.

[0024] The embodiment of the present application provides a composite material, in which AES is introduced as a co-toughening agent of ASA, and the ethylene-propylene rubber in the molecular structure of AES is used to achieve micro-crosslinking of AES and ASA through a crosslinking agent. The micro-crosslinked toughening agent can improve the heat resistance of the entire system while ensuring toughness. Among them, the Vicat softening temperature (50 N, 50°C / min heating rate) of the composite material can reach 105°C or even 106°C, which can meet the use requirements of vehicle body exterior trims.

[0025] In a possible implementation, the mass fraction of EPDM in AES is 20% to 50%.

[0026] The mass fraction of ethylene propylene rubber in AES may be 20%, 25%, 30%, 35%, 40%, 45%, or 50%. Specifically, the mass fraction of ethylene propylene rubber in AES may be 30% to 40%.

[0027] In a possible implementation, the melt index of PMMA is 0.5-20 g / min (230° C., 3.5 kg test conditions).

[0028] The melt index of PMMA may be 0.5 g / min, 1 g / min, 2 g / min, 3 g / min, 5 g / min, 8 g / min, 10 g / min, 12 g / min, 15 g / min, 18 g / min, or 20 g / min. Specifically, the melt index of PMMA may be 2 to 10 g / min.

[0029] In a possible implementation, the mass fraction of acrylic rubber in ASA is 20% to 60%.

[0030] The mass fraction of the acrylate rubber in ASA may be 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, or 60%. Specifically, the mass fraction of the acrylate rubber in ASA may be 40% to 60%.

[0031] In a possible implementation, the cross-linking agent is mainly a peroxide, including at least one of cumene peroxide, hydrogen peroxide, potassium peroxide, and sodium peroxide.

[0032] In the embodiment of the present application, AES and ASA are micro-crosslinked by a cross-linking agent, and the toughening agent after micro-cross-linking is used to improve the problem of decreased heat resistance of the material caused by the addition of ASA.

[0033] In a possible implementation, the compatibilizer is a binary copolymer of any two components of acrylonitrile, styrene and maleic anhydride; or a terpolymer of acrylonitrile, styrene and maleic anhydride.

[0034] In this implementation, if the compatibilizer is a binary copolymer, the compatibilizer may be a binary copolymer of acrylonitrile and styrene, a binary copolymer of acrylonitrile and maleic anhydride, or a binary copolymer of styrene and maleic anhydride.

[0035] The mass fraction of maleic anhydride in the terpolymer or the binary copolymer containing maleic anhydride is 15% to 50%. For example, the mass fraction of maleic anhydride may be 15%, 20%, 25%, 30%, 35%, 40%, 45%, or 50%. Specifically, the mass fraction of maleic anhydride may be 20% to 30%.

[0036] In the embodiments of the present application, the compatibilizer can improve the compatibility among PMMA, AES and ASA, and enhance the overall performance of the PMMA / ASA / AES composite material.

[0037] In a possible implementation, the heat stabilizer includes at least one of a hindered phenol heat stabilizer and a hypophosphite heat stabilizer.

[0038] In this implementation, the heat stabilizer may include at least one of BASF 1010, BASF 1076, BASF 168, BASF 626, and BASF 627.

[0039] In the embodiments of the present application, the thermal stabilizer can significantly prevent the aging of the composite material and extend its service life.

[0040] In a possible implementation, the light stabilizer includes at least one of a hindered amine light stabilizer and an ultraviolet absorber.

[0041] In this implementation, the light stabilizer may include at least one of BASF 770, BASF 944, BASF 234, and BASF UV-P.

[0042] In the embodiments of the present application, the above-mentioned light stabilizer can slow down the possibility of chemical reactions of the PMMA / ASA / AES composite material, and prevent or delay the process of light aging.

[0043] On the other hand, an embodiment of the present application provides a method for preparing a composite material, the preparation method comprising: Step 101: AES and ASA are first mixed uniformly according to the weight proportions of each component, and then a cross-linking agent and 0.05-0.4 parts of a heat stabilizer are added and the mixture is continued to be mixed uniformly to obtain a first mixed material.

[0044] The weight proportions of the heat stabilizer added in step 101 can be 0.05 parts, 0.1 parts, 0.12 parts, 0.15 parts, 0.18 parts, 0.2 parts, 0.22 parts, 0.25 parts, 0.26 parts, 0.3 parts, 0.35 parts, or 0.4 parts.

[0045] In step 101, AES and ASA are first mixed uniformly for 2 to 3 minutes, and then a cross-linking agent and a heat stabilizer are added and mixed uniformly for 5 to 10 minutes, thereby obtaining a first mixed material.

[0046] The mixing time of AES and ASA can be 2 min, 2.5 min, or 3 min, which is not specifically limited. The mixing time after adding the heat stabilizer and the cross-linking agent can be 5 min, 6 min, 7 min, 8 min, 9 min, or 10 min, which is not specifically limited.

[0047] Step 102: Add the first mixed material into a twin-screw extruder at an extrusion temperature in the range of 190-230° C. to obtain a mixture.

[0048] The first mixed material is added into a twin-screw extruder for a slight cross-linking reaction to obtain a slight cross-linked ASA / AES mixture.

[0049] The extrusion temperature can be controlled in nine stages, with each stage being 5°C.

[0050] Step 103: uniformly mix the mixture with PMMA, a compatibilizer, a light stabilizer and 0.05-0.6 parts of a heat stabilizer to obtain a second mixed material.

[0051] The mass fraction of the heat stabilizer added in step 103 can be 0.05 part, 0.1 part, 0.15 part, 0.18 part, 0.2 part, 0.22 part, 0.25 part, 0.3 part, 0.32 part, 0.34 part, 0.4 part, 0.45 part, 0.5 part, 0.55 part, and 0.6 part.

[0052] The mixing time in step 103 can be set and changed as needed, and is not specifically limited thereto. For example, the mixing time is 10 min, 12 min, or 15 min.

[0053] Step 104: adding the second mixed material into a twin-screw extruder at an extrusion temperature in the range of 190-250° C. to obtain a composite material.

[0054] The second mixed material is added into a twin-screw extruder for blending to obtain a PMMA / ASA / AES composite material.

[0055] The extrusion temperature in step 104 can also be controlled in nine stages, with the first five stages being controlled at 5°C intervals and the last four stages being controlled at 10°C intervals.

[0056] In the embodiments of the present application, the particle size of the micro-crosslinked material can be controlled to be below 5 μm by controlling the peroxide content, extrusion temperature, screw combination, etc., and 90% of the particle sizes of the micro-crosslinked material are below 1 μm.

[0057] The technical solution of the present application will be described in detail below through specific embodiments.

[0058] In the following specific examples, operations involved without specifying conditions were performed under conventional conditions or conditions recommended by the manufacturer.

[0059] Wherein, the cross-linking agent in Examples 1 to 6 and Comparative Examples 1 to 4 is cumene peroxide; The compatibilizer in Examples 1 to 3 and Comparative Examples 2 to 3 is a binary copolymer of acrylonitrile and maleic anhydride, wherein the mass fraction of acrylonitrile is 75% and the mass fraction of maleic anhydride is 25%. The compatibilizer in Examples 4 to 6 and Comparative Examples 1 and 4 is a terpolymer of acrylonitrile, styrene and maleic anhydride, wherein the mass fraction of acrylonitrile is 55%, the mass fraction of styrene is 20% and the mass fraction of maleic anhydride is 25%. The heat stabilizers in Examples 1 to 6 and Comparative Examples 1 to 4 are all mixtures of BASF 1010, BASF 168 and BASF 626, wherein the mass fraction of BASF 1010 is 80%, the mass fraction of BASF 168 is 10%, and the mass fraction of BASF 626 is 10%; The light stabilizers in Examples 1 to 6 and Comparative Examples 1 to 4 are all mixtures of BASF 770, BASF 944, BASF 234 and BASF UV-P, wherein the mass fraction of BASF 770 is 40%, the mass fraction of BASF 944 is 30%, the mass fraction of BASF 234 is 20%, and the mass fraction of BASF UV-P is 10%.

[0060] Example 1 Example 1 provides a PMMA / ASA / AES composite material, which is obtained by the following preparation method: (1) First, 10 parts of AES and 20 parts of ASA were mixed evenly for 3 minutes, and then 0.1 parts of heat stabilizer and 0.3 parts of cross-linking agent were added and continued to mix evenly for 10 minutes to obtain a first mixed material.

[0061] (2) Adding the first mixed material into a twin-screw extruder at an extrusion temperature of 190-230° C. to obtain a mixture.

[0062] (3) The mixture was mixed evenly with 70 parts of PMMA, 3 parts of a compatibilizer, 0.1 parts of a heat stabilizer and 0.5 parts of a light stabilizer to obtain a second mixed material.

[0063] (4) Adding the second mixed material into a twin-screw extruder at an extrusion temperature of 190-250° C. to obtain a composite material.

[0064] The specific composition of Example 1 can also be found in Table 1. Correspondingly, the specific compositions of subsequent Examples 2 to 6 and Comparative Examples 1 to 4 can also be found in Table 1.

[0065] Table 1

[0066] Example 2 Example 2 provides a PMMA / ASA / AES composite material, which is obtained by the following preparation method: (1) First, 15 parts of AES and 15 parts of ASA were mixed evenly for 3 minutes, and then 0.1 parts of heat stabilizer and 0.5 parts of cross-linking agent were added and continued to mix evenly for 10 minutes to obtain a first mixed material.

[0067] (2) Adding the first mixed material into a twin-screw extruder at an extrusion temperature of 190-230° C. to obtain a mixture.

[0068] (3) The mixture was mixed evenly with 70 parts of PMMA, 3 parts of a compatibilizer, 0.1 parts of a heat stabilizer and 0.5 parts of a light stabilizer to obtain a second mixed material.

[0069] (4) Adding the second mixed material into a twin-screw extruder at an extrusion temperature of 190-250° C. to obtain a composite material.

[0070] Example 3 Example 3 provides a PMMA / ASA / AES composite material, which is obtained by the following preparation method: (1) First, 10 parts of AES and 20 parts of ASA were mixed evenly for 3 minutes, and then 0.12 parts of heat stabilizer and 0.6 parts of cross-linking agent were added and continued to mix evenly for 10 minutes to obtain a first mixed material.

[0071] (2) Adding the first mixed material into a twin-screw extruder at an extrusion temperature of 190-230° C. to obtain a mixture.

[0072] (3) The mixture was mixed evenly with 70 parts of PMMA, 3 parts of a compatibilizer, 0.18 parts of a heat stabilizer and 0.5 parts of a light stabilizer to obtain a second mixed material.

[0073] (4) Adding the second mixed material into a twin-screw extruder at an extrusion temperature of 190-250° C. to obtain a composite material.

[0074] Example 4 Example 4 provides a PMMA / ASA / AES composite material, which is obtained by the following preparation method: (1) First, 15 parts of AES and 20 parts of ASA were mixed evenly for 3 minutes, and then 0.18 parts of heat stabilizer and 0.6 parts of cross-linking agent were added and continued to mix evenly for 10 minutes to obtain a first mixed material.

[0075] (2) Adding the first mixed material into a twin-screw extruder at an extrusion temperature of 190-230° C. to obtain a mixture.

[0076] (3) The mixture was mixed evenly with 65 parts of PMMA, 5 parts of a compatibilizer, 0.22 parts of a heat stabilizer and 0.5 parts of a light stabilizer to obtain a second mixed material.

[0077] (4) Adding the second mixed material into a twin-screw extruder at an extrusion temperature of 190-250° C. to obtain a composite material.

[0078] Example 5 Example 5 provides a PMMA / ASA / AES composite material, which is obtained by the following preparation method: (1) First, 10 parts of AES and 25 parts of ASA were mixed evenly for 3 minutes, and then 0.22 parts of heat stabilizer and 0.8 parts of cross-linking agent were added and continued to mix evenly for 10 minutes to obtain a first mixed material.

[0079] (2) Adding the first mixed material into a twin-screw extruder at an extrusion temperature of 190-230° C. to obtain a mixture.

[0080] (3) The mixture was mixed evenly with 65 parts of PMMA, 5 parts of a compatibilizer, 0.28 parts of a heat stabilizer and 0.5 parts of a light stabilizer to obtain a second mixed material.

[0081] (4) Adding the second mixed material into a twin-screw extruder at an extrusion temperature of 190-250° C. to obtain a composite material.

[0082] Example 6 Example 6 provides a PMMA / ASA / AES composite material, which is obtained by the following preparation method: (1) First, 20 parts of AES and 15 parts of ASA were mixed evenly for 3 minutes, and then 0.12 parts of heat stabilizer and 0.8 parts of cross-linking agent were added and continued to mix evenly for 10 minutes to obtain a first mixed material.

[0083] (2) Adding the first mixed material into a twin-screw extruder at an extrusion temperature of 190-230° C. to obtain a mixture.

[0084] (3) The mixture was mixed evenly with 65 parts of PMMA, 5 parts of a compatibilizer, 0.18 parts of a heat stabilizer and 0.5 parts of a light stabilizer to obtain a second mixed material.

[0085] (4) Adding the second mixed material into a twin-screw extruder at an extrusion temperature of 190-250° C. to obtain a composite material.

[0086] Comparative Example 1 Comparative Example 1 provides a PMMA / ASA / AES composite material, which is obtained by the following preparation method: (1) First, 20 parts of AES and 5 parts of ASA were mixed evenly for 3 minutes, and then 0.26 parts of heat stabilizer and 1.0 parts of cross-linking agent were added and continued to mix evenly for 10 minutes to obtain a first mixed material.

[0087] (2) Adding the first mixed material into a twin-screw extruder at an extrusion temperature of 190-230° C. to obtain a mixture.

[0088] (3) The mixture was mixed evenly with 75 parts of PMMA, 5 parts of a compatibilizer, 0.34 parts of a heat stabilizer and 0.5 parts of a light stabilizer to obtain a second mixed material.

[0089] (4) Adding the second mixed material into a twin-screw extruder at an extrusion temperature of 190-250° C. to obtain a composite material.

[0090] Comparative Example 2 Comparative Example 2 provides a PMMA / ASA composite material, which is obtained by the following preparation method: (1) 30 parts of ASA, 0.1 parts of heat stabilizer and 0.3 parts of cross-linking agent were mixed uniformly for 10 min to obtain a first mixed material.

[0091] (2) Adding the first mixed material into a twin-screw extruder at an extrusion temperature of 190-230° C. to obtain a mixture.

[0092] (3) The mixture was mixed evenly with 70 parts of PMMA, 3 parts of a compatibilizer, 0.1 parts of a heat stabilizer, and 0.5 parts of a light stabilizer to obtain a second mixed material.

[0093] (4) Adding the second mixed material into a twin-screw extruder at an extrusion temperature of 190-250° C. to obtain a composite material.

[0094] Comparative Example 3 Comparative Example 3 provides a PMMA / ASA / AES composite material, which is obtained by the following preparation method: (1) 26 parts of ASA and 4 parts of AES were mixed evenly for 3 min, and then 0.1 parts of heat stabilizer and 0.3 parts of cross-linking agent were added and continued to mix evenly for 10 min to obtain a first mixed material.

[0095] (2) Adding the first mixed material into a twin-screw extruder at an extrusion temperature of 190-230° C. to obtain a mixture.

[0096] (3) The mixture was mixed evenly with 70 parts of PMMA, 3 parts of a compatibilizer, 0.1 parts of a heat stabilizer, and 0.5 parts of a light stabilizer to obtain a second mixed material.

[0097] (4) Adding the second mixed material into a twin-screw extruder at an extrusion temperature of 190-250° C. to obtain a composite material.

[0098] Comparative Example 4 Comparative Example 4 provides a PMMA / ASA / AES composite material, which is obtained by the following preparation method: (1) 5 parts of ASA and 25 parts of AES were mixed uniformly for 3 minutes, and then 0.26 parts of heat stabilizer and 1.0 parts of cross-linking agent were added and continued to mix uniformly for 10 minutes to obtain a first mixed material.

[0099] (2) Adding the first mixed material into a twin-screw extruder at an extrusion temperature of 190-230° C. to obtain a mixture.

[0100] (3) The mixture was mixed evenly with 70 parts of PMMA, 5 parts of a compatibilizer, 0.34 parts of a heat stabilizer, and 0.5 parts of a light stabilizer to obtain a second mixed material.

[0101] (4) Adding the second mixed material into a twin-screw extruder at an extrusion temperature of 190-250° C. to obtain a composite material.

[0102] Application Examples The present application tests the composite materials prepared in Examples 1 to 6 and Comparative Examples 1 to 4. The test results are shown in Table 2.

[0103] Table 2

[0104] The test method for simply supported beam notched impact is carried out in accordance with ISO 179-1 / 1 eA, and the test method for Vicat softening temperature is carried out in accordance with ISO 306 / B 50.

[0105] It can be seen from Table 2 that the simply supported beam notched impact strength and Vicat softening temperature of the composite materials prepared in Examples 1 to 6 are significantly better than those in Comparative Example 2, especially the Vicat softening temperature of the composite material prepared in Example 2 is as high as 106°C. This is because an appropriate amount of AES is added to the composite materials prepared in Examples 1 to 6, and the ethylene propylene rubber in the AES is micro-crosslinked with the ASA, thereby improving the heat resistance of the overall system while ensuring the toughness of the material.

[0106] Although AES is also added in Comparative Example 3, the amount of AES added is relatively small. Therefore, the composite material prepared in Comparative Example 3 has relatively low notched impact strength and Vicat softening temperature. Although the composite materials prepared in Comparative Examples 1 and 4 also have relatively high notched impact strength and Vicat softening temperature, the amount of ASA added in Comparative Example 1 is relatively small, and the amount of AES added in Comparative Example 4 is relatively large, both of which result in the appearance of the products not meeting the requirements. It can be seen that the weight percentage of ASA and the weight percentage of AES have a very important influence on the appearance and performance of the product.

[0107] The above description is only for the purpose of facilitating the technical solution of the present application to be understood by those skilled in the art, and is not intended to limit the present application. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present application shall be included in the protection scope of the present application.

Claims

1. A composite material, characterized in that: The composite material comprises the following components in parts by weight: 50-90 parts of polymethyl methacrylate PMMA, 10-40 parts of acrylonitrile-styrene-acrylate copolymer ASA, 5-20 parts of ethylene-propylene-styrene-acrylonitrile copolymer AES, 0.1-3 parts of crosslinking agent, 0.1-1 parts of heat stabilizer, 1-10 parts of compatibilizer, and 0.1-3 parts of light stabilizer.

2. The composite material according to claim 1, characterized in that The mass fraction of ethylene propylene rubber in the AES is 20% to 50%.

3. The composite material according to claim 1, characterized in that The melt index of the PMMA is 0.5-20 g / min.

4. The composite material according to claim 1, characterized in that The mass fraction of the acrylic rubber in the ASA is 20% to 60%.

5. The composite material according to claim 1, characterized in that The cross-linking agent includes at least one of cumene peroxide, hydrogen peroxide, potassium peroxide, and sodium peroxide.

6. The composite material according to claim 1, characterized in that The compatibilizer is a binary copolymer of any two components of acrylonitrile, styrene and maleic anhydride; or a terpolymer of acrylonitrile, styrene and maleic anhydride.

7. The composite material according to claim 6, characterized in that The mass fraction of the maleic anhydride in the terpolymer or the binary copolymer containing the maleic anhydride is 15% to 50%.

8. The composite material according to claim 1, characterized in that The heat stabilizer includes at least one of a hindered phenol heat stabilizer and a hypophosphite heat stabilizer.

9. The composite material according to claim 1, characterized in that: The light stabilizer includes at least one of a hindered amine light stabilizer and an ultraviolet absorber.

10. A method for preparing the composite material according to any one of claims 1 to 9, characterized in that: The preparation method comprises: According to the weight proportion of each component, the AES and the ASA are first mixed uniformly, and then the cross-linking agent and 0.05-0.4 parts of the heat stabilizer are added and continued to be mixed uniformly to obtain a first mixed material; Adding the first mixed material into a twin-screw extruder at an extrusion temperature in the range of 190-230° C. to obtain a mixture; The mixture is uniformly mixed with the PMMA, the compatibilizer, the light stabilizer and 0.05-0.6 parts of the heat stabilizer to obtain a second mixed material; The second mixed material is added into the twin-screw extruder at an extrusion temperature in the range of 190-250° C. to obtain the composite material.

Citation Information

Patent Citations

  • Preparation method for one-dimensional magnetic thermo-sensitivity nanochain

    CN102417567A

  • Thermoplastic resin blend with weather resistance, scratch resistance, high gloss and high heat resistance and preparation method of the resin blend

    CN102604299A

  • Efficient anti-mildew AES (Acrylonitrile-Ethylene-propylene-diene-terpolymer rubber-Styrene) resin composition and preparation method thereof

    CN107245214A

  • AES-PMMA composite material and preparation method thereof

    CN108976687A

  • Resin composition and molded article

    CN119343403A

Cited By

  • Polymer composite material for high-comfort automobile seat cover and preparation method of polymer composite material

    CN120758022A

  • High-comfort automobile seat cover made of polymer composite material and preparation method thereof

    CN120758022B

  • Composite material and preparation method therefor

    WO2026188775A1